A case study on thermal performance analysis of a solar still basin employing ceramic magnets - Dhivagar, Ramasamy; El-Sapa, Shreen; Alrubaie, Ali Jawad; Al-khaykan, Ameer; Chamkha, Ali J.; Panchal, Hitesh; El-Sebaey, Mahmoud S.; sharma, Kamal (Case studies in thermal engineering, 2022)
The energy and exergy analysis of a single slope solar stills using ceramic type rectangular and circular magnets in the basin was carried out in this study and compared to conventional solar still. The results showed that the rectangular magnet solar still (RMSS) had higher hourly productivity of about 5.8% and 13.7% than circular magnet solar still (CMSS) and conventional solar still (CSS), respectively. For 12 h of reading, the cumulative productivity in RMSS, CMSS, and CSS was observed at 3.15 kg/m2, 2.82 kg/m2, and 2.15 kg/m2, respectively. Compared to CMSS and CSS, the RMSS has enhanced its energy efficiency by 4.9% and 6.9%, respectively. The observed exergy efficiency in RMSS has increased to 3.4% and 17.2%, respectively, than CMSS and CSS. Due to sensible heat absorbed by magnets, the amount of exergy lost in the RMSS and CMSS basin is much less than in CSS. In economic analysis, the estimated produced water cost (PWC) of RMSS is 4.5% and 22.2% lower than the PWC estimated in CMSS and CSS, respectively. Overall, the results showed that the magnetization of saline water made the solar still work much better. [Display omitted]